Regional burden of chronic kidney disease in North Africa and Middle East during 1990–2019; Results from Global Burden of Disease study 2019 - Tabatabaei-Malazy, Ozra; Saeedi Moghaddam, Sahar; Khashayar, Patricia; Keykhaei, Mohammad; Tehrani, Yeganeh Sharifnejad; Malekpour, Mohammad-Reza; Esfahani, Zahra; Rashidi, Mohammad-Mahdi; Golestani, Ali; Shobeiri, Parnian; Moghimi, Mana; Gorgani, Fateme; et al. (Frontiers in Public Health, 2022)
Objectives Updating burden data of chronic kidney disease (CKD) as one of the most prevalent non-communicable diseases is essential for proper provision of healthcare by policymakers. We aimed to estimate the burden of CKD and its attributed burden in North Africa and Middle East region (NAME) during 1990–2019. Methods The CKD-related Global Burden of Disease (GBD) 2019 estimates were extracted from Health Metrics and Evaluation (IHME) website. Results In 2019, 2,034,879 new CKD cases (95% Uncertainty interval 1,875,830 to 2,202,724) with an age-standardized incidence rate of 447.5 (415.1 to 482.8) per 100,000 was reported, showing a 70.9% increase in the past 30 years. CKD led to 111,812 deaths (96,421 to 130,853) with an age-standardized rate of 30.4 (26.3 to 35.4) per 100,000. The highest increase and decrease in the mortality rate were estimated in Morocco 21.8% (−8.9 to 51.6) and Kuwait −41.5% (−51.2 to −29.1). In 2019, CKD was responsible for 744.4 (646.1 to 851.8) age-standardized disability-adjusted life years (DALYs), mostly contributed to “other and unspecified causes” [237.2 (191.1 to 288.4)], type 2 diabetes [205.9 (162.4 to 253.6)], and hypertension [203.3 (165.8 to 243)]. An increase was noted in DALYs from ages 25–29 and surged with an accelerating pattern by age. Kidney dysfunction, high systolic blood pressure, and high body mass index ranked as the top three risk factors for the disorder. Conclusions Our study raised an alarm regarding the increasing CKD burden in NAME. There is an urgency to deal with hypertension and overweight/obesity at the primary care level, implementing CKD screening for at-risk groups, and facilitating the accessibility to appropriate treatments.